Sauropodomorph dinosaur trackways from the Fleming Fjord Formation of East Greenland: Evidence for Late Triassic sauropods - Lallensack, Jens N.; Klein, Hendrik; Milàn, Jesper; Wings, Oliver; Mateus, Octávio; Clemmensen, Lars B. (Zenodo, 2017)
Lallensack, Jens N., Klein, Hendrik, Milàn, Jesper, Wings, Oliver, Mateus, Octávio, Clemmensen, Lars B. (2017): Sauropodomorph dinosaur trackways from the Fleming Fjord Formation of East Greenland: Evidence for Late Triassic sauropods. Acta Palaeontologica Polonica 62 (4): 833-843, DOI:10.4202/app.00374.2017, URL: http://dx.doi.org/10.4202/app.00374.2017